1963
DOI: 10.2118/457-pa
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Pressure on Forward and Reverse Combustion

Abstract: Experiments have been performed in a linear near-adiabatic system for the purpose of extending data on reverse and forward combustion from atmospheric pressure to 1,000 psig.Results obtained from reverse combustion appear to conform qualitatively with the existing description of the process when reaction kinetics are suitably modified to account for the increase in pressure, z. e., increasing the pressure decreases the peak temperature and increases the combustion zone velocity.Forward combustion appears to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

1965
1965
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 0 publications
4
16
0
Order By: Relevance
“…This behavior agrees with the experimental findings of Wilson, et aI. 22 On the other hand, the velocity of the combustion zone is about half the experimentally measured value, and the maximum combustion temperatur:e increases slowly instead of maintaining a constant value, as observed experimentally. The complexity of the mathematical model precludes attributing these differences to a specific source of error.…”
Section: Society Of Petroleum Engineers Journalsupporting
confidence: 92%
See 3 more Smart Citations
“…This behavior agrees with the experimental findings of Wilson, et aI. 22 On the other hand, the velocity of the combustion zone is about half the experimentally measured value, and the maximum combustion temperatur:e increases slowly instead of maintaining a constant value, as observed experimentally. The complexity of the mathematical model precludes attributing these differences to a specific source of error.…”
Section: Society Of Petroleum Engineers Journalsupporting
confidence: 92%
“…An examination of the corresponding oil and water production histories and the air-oil ratios support this conclusion. These results are corroborated by the experimental findings of Wilson, et al 22 The oil and water production histories and the air-oil ratios are affected by the above variations in Z, m and n in a manner similar to the temperature profiles. ""I...J U lD lD in Fig.…”
Section: The Predicted Cumulative Oil and Water Productionsupporting
confidence: 82%
See 2 more Smart Citations
“…A large number of studies on the structure of the combustion front have been reported since 1950s, see [1,2,3,4,5,6,8,20,21,23,26], for instance. These studies did not take into account other waves that occur in the combustion problem.…”
Section: Introductionmentioning
confidence: 99%